Deconstruction of a Dialogue - Steven Burik (Asian Studies, 2023)
It is common knowledge that Martin Heidegger’s attempts at engaging non-Western philosophy are very much a construct of his own making. This article in no way seeks to disagree with those observations, but argues two things: first, that Heidegger’s “dialogue” with his two main other sources of inspiration, the ancient Greek thinkers and the German poets, is not different in kind or in principle from his engagement with East Asia. One can of course quite easily argue that Heidegger’s main interest was the ancient Greek thinkers, and then the poets, and only lastly Asia. But this hierarchy in preference does not make Heidegger’s approach different in kind or in principle. Second, I argue that there is an important place in comparative philosophy for the type of thinking displayed by Heidegger in this kind of Auseinandersetzung (confrontation) with—and “appropriation” of—Asian (or Greek, or Poetic) thought.